2020
DOI: 10.3389/fpubh.2020.00253
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students and COVID-19: Knowledge, Attitudes, and Precautionary Measures. A Descriptive Study From Jordan

Abstract: The recent coronavirus disease (COVID-19) pandemic is associated with increasing morbidity and mortality and has impacted the lives of the global populations. Human behavior and knowledge assessment during the crisis are critical in the overall efforts to contain the outbreak. To assess knowledge, attitude, perceptions, and precautionary measures toward COVID-19 among a sample of medical students in Jordan. This is a cross-sectional descriptive study conducted between the 16th and 19th of March 2020. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

97
315
21
24

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(457 citation statements)
references
References 29 publications
97
315
21
24
Order By: Relevance
“…Similarly, the respondents' level of self-reported preventive behaviour signi cantly differed according to their sex, occupation, years of working experience and educational level. These results are in agreement with the results of Rahman and Sathi [20] on the variation of respondents' preventive behavior according to the different age groups, Al-Hanawi et al [25] in regard to the respondents' gender, Saqlain et al [21] regarding the respondents' years of working experience and Khasawneh et al [26] in relation to the respondents' educational level.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, the respondents' level of self-reported preventive behaviour signi cantly differed according to their sex, occupation, years of working experience and educational level. These results are in agreement with the results of Rahman and Sathi [20] on the variation of respondents' preventive behavior according to the different age groups, Al-Hanawi et al [25] in regard to the respondents' gender, Saqlain et al [21] regarding the respondents' years of working experience and Khasawneh et al [26] in relation to the respondents' educational level.…”
Section: Discussionsupporting
confidence: 90%
“…In particular, knowledge of all three key symptoms, and lack of treatment and vaccines was high which could potentially impact behaviours. As in the WHO survey [33], but in contrast to other studies [49,59,60], this study did not assess knowledge of transmission measures, because of uncertainties in the general public domain at the time about modes of transmission. In addition, participants exhibited high levels of knowledge of the effectiveness of hand hygiene and social distancing measures in preventing infection, with 90.7% and 93.5% respectively correctly identifying of all or all but one measure.…”
Section: Investigation Of Knowledge/socio-cognitive Perception Towardmentioning
confidence: 99%
“…In the 2 studies of university populations during the COVID-19 pandemic, only risk perception [48] and gender and economic category [49] have been demonstrated as determinants of protective behaviour. However, in university students in previous pandemics, social norms and self-e cacy [25], perceived threat or concern [23,59], empathic responding [21], course [20] and country of birth [24] have been additionally identi ed as determinants.…”
Section: Investigation Of the Determinants Explaining Hand Hygiene Anmentioning
confidence: 99%
“…These ndings were also seen in a study done among university students in Jordan. [20] Studies have shown that availability of information in mass and social media can be a source of information for the students. [22] Respondents, (91.5%) were also aware of the cautionary actions, self-isolation period as per WHO guidelines and the effective use of mask for preventing corona infection (94.3%).…”
Section: Resultsmentioning
confidence: 99%
“…Similar method was used in another study, where class representatives were also involved in forwarding and sharing the questionnaire link to their friends. [20] Students completed the questionnaire at leisure within the period of the study. They signed an integrity pledge that they will answer the questions by themselves and would not consult other resources and with their friends and family members while answering the same.…”
Section: Methodsmentioning
confidence: 99%